Modes of Brain Cell Death Following Intracerebral Hemorrhage - Zhang, Yan; Khan, Suliman; Liu, Yang; Zhang, Ruiyi; Li, Hongmin; Wu, Guofeng; Tang, Zhouping; Xue, Mengzhou; Yong, V. Wee (Frontiers in Cellular Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is a devastating form of stroke with high rates of mortality and morbidity. It induces neuronal cell death that is responsible for neurological deficits post-injury. There are no therapies that effectively mitigate cell death to treat ICH. This review aims to summarize our knowledge of ICH-induced cell death with a focus on apoptosis and necrosis. We also discuss the involvement in ICH of recently described modes of cell death including necroptosis, pyroptosis, ferroptosis, autophagy and parthanatos. We summarize treatment strategies to mitigate brain injury based on particular cell death pathways after ICH.